Dinamika Ekonomi dan Peluang Kerja Rumah Tangga Perkebunan Rakyat di Kabupaten Tanjung Jabung Barat - Amril Amril; Erfit Erfit; Yulmardi Yulmardi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
This study aimed to analyze: (1) to analyze the economic dynamics of the household smallholder plantation in Tanjung Jabung Barat which include changes in household assets, expenditure and consumption patterns of the household; (2) to analyze the dynamics of domestic employment opportunities household smallholder plantation in Tanjung Jabung Barat which includes changes in working hours and employment status both of head or household members. The main data used in this study is raw data SUSENAS Year 2010 and 2014. Descriptive data were analyzed quantitatively using a single frequency tables. The research found that: 1) During the period from year 2010 to 2014, the general economic welfare of households smallholder plantations in Tanjung Jabung Barat has shown. This can be seen from the aspect of increasing ownership and quality of housing and the ownership of productive assets and other household assets. In addition, the increase in prosperity is also evident from the increase in household expenditures and changes in food consumption patterns and non-food; 2) In terms of working hours devoted a good show that a relatively large proportion of heads of households and household members who work above the normal working hours. Allocation of long working hours is one of the survival strategies of households smallholder plantations in Tanjung Jabung Barat; 3) From the job status shows most heads of households trying to temporary laborers/workers are not paid. These unpaid workers generally are members of the household